2018
DOI: 10.4028/www.scientific.net/kem.778.195
|View full text |Cite
|
Sign up to set email alerts
|

Resistivity Enhancement of Sr-Hexaferrite Using Rare Earth Dopant to Minimize Energy Losses

Abstract: Strontium hexaferrite is a material of choice due its various magnetic applications. Energy losses are a prominent issue in these magnetic materials. To lower these energy losses, we need to improve the resistivity by reducing eddy current losses. In this work nanoparticles of Gadolinium (Gd) doped Sr-hexaferrite (SrFe12-xGdxO19 x =0 .0, 0.1) have been synthesized by co-precipitation method. Structural analysis was done by using X-ray diffraction technique (XRD). It was found that the formation of single phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Doping elements such as Ce, Zn, Mn, Sm, Co, Yb, and Gd has been carried out, in each of which the effects of the doped element on the magnetic behavior and electrical properties of the structure have been studied. [16][17][18] Studies on garnet and perovskites and other magnetic nano-particles have also shown that doping the above elements has a significant effect on their thermal stability, crystallization, physical, magnetic, and optical properties. [19][20][21][22] The carrier doping positive effects on the magnetic properties of defective graphene have been detected.…”
Section: Introductionmentioning
confidence: 99%
“…Doping elements such as Ce, Zn, Mn, Sm, Co, Yb, and Gd has been carried out, in each of which the effects of the doped element on the magnetic behavior and electrical properties of the structure have been studied. [16][17][18] Studies on garnet and perovskites and other magnetic nano-particles have also shown that doping the above elements has a significant effect on their thermal stability, crystallization, physical, magnetic, and optical properties. [19][20][21][22] The carrier doping positive effects on the magnetic properties of defective graphene have been detected.…”
Section: Introductionmentioning
confidence: 99%